Peran Supervisi Islami Dalam Pengembangan Profesionalisme Guru - Isranaini, Resti (CV JK Riset Publishing Group, 2026)
This study examines the role of Islamic supervision in developing teacher professionalism in Islamic educational institutions. The research background is based on the urgent need for a supervision model that is not only administratively oriented, but also carries spiritual and pedagogical values. The purpose of this study is to analyze the implementation of Islamic supervision and its influence on enhancing teachers' professional competence. The method used is qualitative with a case study approach in three public madrasah aliyah. Data were collected through in-depth interviews, participatory observation, and documentation studies. The results show that Islamic supervision emphasizing the values of ukhuwah, amanah, and tauladan is able to significantly increase teachers' intrinsic motivation. Madrasah principals who apply Islamic value-based supervision succeeded in creating a conducive and collaborative academic climate. It is concluded that Islamic supervision is an effective holistic approach to improving teacher professionalism in madrasah